Pengaruh Layanan Bimbingan Kelompok dengan Teknik Psikodrama Cerita Rakyat Nusantara untuk Mengurangi Perilaku Agresif Siswa - Nuril Fata Mahwiyah; Tri Umari; Donal Donal (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
This research is motivated by the phenomenon of the high tendency of aggressive behavior among students and their peers, especially among students at the junior high school level. This study aims to determine the effect of group guidance services using the Indonesian folklore psychodrama technique to reduce students' aggressive behavior as an effort to facilitate students to express their reactions to their pressure without using aggressive behavior. This research is a quantitative research with the One Group Pretest-Posttest experimental method. The implementation of this research was carried out at MTsN 1 Pekanbaru with a sample of 12 people from a total population of 440 seventh grade students. The results of the data obtained in this study were then calculated using descriptive statistical analysis techniques and tested for their influence using the Wilcoxon test formula and the N-Gain test. The result of the Gain Score calculation is 0.68 which can be interpreted that the magnitude of the influence of group guidance services using the Indonesian folklore psychodrama technique on students' aggressive behavior is in the moderate category. Based on this, it can be said that group guidance services using the Indonesian folklore psychodrama technique have an effect in reducing students' aggressive behavior.